Tareas extraclases y su influencia en el desarrollo de habilidades cognitivas en los estudiantes de la escuela de educación básica Las Paralelas del sector San Antonio del cantón Camilo Ponce Enríquez de la provincia del Azuay, periodo 2012-2013. - Cruz Castillo, Katiuska Catherine (2015)
This research "extraclases Tasks and their influence on the development of cognitive skills in students of basic school education sector The Parallel San Antonio Canton Camilo Ponce Enríquez Azuay province, period 2012-2013". The extraclases tasks are the experiences in the classrooms of our country for this reason it took many emphasis to phase in leaps and bounds this situation to make education more competitive in the teaching-learning process, to achieve inclusive education covering globalizers issues.